Tinjauan Yuridis Putusan Nomor 450/Pid.B/2022/PN Bdg Tentang Tindak Pidana Menyerang Kehormatan Kesusilaan - Muhammad Fikri Azka; Dian Andriasari (Bandung Conference Series: Law Studies, 2023)
Abstract. Criminal acts of obscenity and rape are criminal acts in the realm of decency. The criminal act of obscenity is an act of decency which has a broad meaning, in distinguishing obscenity from attempted rape it can be seen from the intention of the accused. In a case of decency crime, the judge needs to be careful and careful in differentiating the crime committed by the defendant by paying attention to the facts of the trial and the evidentiary process. Is the classification of the actions carried out by the defendant included in Article 285 Jo. 53 paragraph (1) of the Criminal Code concerning attempted rape or is it included in Article 289 of the Criminal Code concerning obscene acts. The problem is that it is difficult to distinguish between the two crimes because the element of rape is no longer relevant today. This research uses normative juridical method. In collecting data, researchers used library data techniques sourced from laws and regulations, books, official documents, publications, and research results relevant to the research topic. The results of the research by the authors of the crime committed by the defendant based on decision number 450/Pid.B/2022/PN Bdg are more directed at the crime of attempted rape because by looking at the facts of the existing trial. The public prosecutor's indictment is more appropriate if the charge against the defendant is a criminal act of attempted rape or Article 285 Jo. 53 paragraph (1) of the Criminal Code. Then in the process of proving the crime of attempted rape it should have been fulfilled because the most important element in the trial is intention and it is already real. However, in the process of proving the crime of attempted rape, it is very difficult to prove at this time because according to the authors and the results of the research prove that the contents of Article 285 concerning rape and 53 paragraph (1) concerning attempts are no longer relevant today. There needs to be a revision of the renewal funds in the meaning of the two articles so that the legal goal, namely justice, can be realized. Abstrak. Tindak pidana perbuatan cabul dan perkosaan merupakan tindak pidana dalam ranah kesusilaan. Tindak pidana perbuatan cabul adalah tindakan kesusilaan yang mempunyai arti yang luas, dalam membedakan perbuatan cabul dengan percobaan perkosaan dapat dilihat dari niat terdakwa. Dalam suatu kasus tindak pidana kesusilaan hakim perlu teliti dan cermat dalam membedakan tindak pidana yang dilakukan oleh terdakwa dengan memperhatikan fakta persidangan dan proses pembuktian. Apakah klasifikasi tindakan yang dilakukan terdakwa termasuk dalam Pasal 285 Jo. 53 ayat (1) KUHP tentang percobaan perkosaan ataukah masuk dalam Pasal 289 KUHP tentang perbuatan cabul. Yang menjadi permasalahan adalah sulitnya membedakan kedua tindak pidana tersebut karena unsur delik perkosaan yang sudah tidak relevan lagi di masa sekarang. Penelitian ini menggunakan metode yuridis normative. Dalam pengumpulan data, peneliti menggunakan teknik data kepustakaan yang bersumber dari peraturan perundang-undangan, buku-buku, dokumen resmi, publikasi, dan hasil penelitian yang relevan dengan topik penelitian. Hasil penelitian penulis tindak pidana yang dilakukan oleh terdakwa berdasarkan putusan nomor 450/pid.b/2022/pn bdg lebih mengarah pada tindak pidana percobaan perkosaan karena dengan melihat fakta persidangan yang ada. Dakwaan penuntut umum lebih tepat apabila dakwaan terhadap terdakwa merupakan tindak pidana percobaan perkosaan atau Pasal 285 Jo. 53 ayat (1) KUHP. Kemudian dalam proses pembuktian tindak pidana percobaan perkosaan seharusnya sudah terpenuhi karena unsur terpenting dalam percobaan ialah niat dan itu sudah nyata adanya. Akan tetapi dalam proses pembuktian tindak pidana percobaan perkosaan untuk saat ini sangat sulit untuk di buktikan karena menurut penulis dan hasil penelitian membuktikan bahwa kandungan pasal 285 tentang perkosaan dan 53 ayat (1) tentang percobaan sudah tidak relevan lagi untuk zaman sekarang. Perlu adanya revisi dana pembaharuan dalam pemaknaan kedua pasal tersebut agar tujuan hukum yaitu keadilan dapat terwujud.